2019
DOI: 10.1002/app.47744
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐based epoxy/polyaniline nanofiber‐carbon dot nanocomposites as advanced anticorrosive materials

Abstract: Application of anticorrosive coating on metal surface enhances the durability of the metal. Anticorrosion can be achieved by the incorporation of conducting nanomaterials like polyaniline or its nanohybrid to a coating material. Thus, bio‐based epoxy nanocomposites were fabricated by the in situ method using polyaniline nanofiber‐carbon dot nanohybrid (0.50 and 1 wt % with respect to epoxy), as the anticorrosive material. The epoxy resin was obtained by polycondensation of bisphenol‐A, sorbitol, and monoglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…[82] Figure 8 showed the modified epoxy resin coatings immersed in 5% HCl and it was found that amine-cured systems exhibited better resistance to diluted bases, whereas anhydride-cured systems displayed better resistance to diluted acids. Saikia et al [83] prepared anticorrosive bio-based epoxy nanocomposites composed of polyaniline nanofiber (PN)-carbon dot (CD) nanohybrid (PC). They evaluated the chemical resistance of films in acidic, basic, and salty chemical environments via weight loss method.…”
Section: Chemical Resistance Performancementioning
confidence: 99%
See 2 more Smart Citations
“…[82] Figure 8 showed the modified epoxy resin coatings immersed in 5% HCl and it was found that amine-cured systems exhibited better resistance to diluted bases, whereas anhydride-cured systems displayed better resistance to diluted acids. Saikia et al [83] prepared anticorrosive bio-based epoxy nanocomposites composed of polyaniline nanofiber (PN)-carbon dot (CD) nanohybrid (PC). They evaluated the chemical resistance of films in acidic, basic, and salty chemical environments via weight loss method.…”
Section: Chemical Resistance Performancementioning
confidence: 99%
“…Saikia et al. [ 83 ] prepared anticorrosive bio‐based epoxy nanocomposites composed of polyaniline nanofiber (PN)‐carbon dot (CD) nanohybrid (PC). They evaluated the chemical resistance of films in acidic, basic, and salty chemical environments via weight loss method.…”
Section: Analysis Of Bio Epoxy Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse nanoparticle identities have been demonstrated for anticorrosion, lling the interstitial spaces of the polymer insulator and preventing ion penetration at the coating-metal interface. A variety of nanoparticles including Fe 3 O 4 , 123 ZnO, 124 clay, 125,126 silica, 109 and carbon nanotubes [127][128][129] have been utilized for anticorrosive applications. In addition, nanoparticles have been widely reported in the introduction of antibacterial activity.…”
Section: Nanoparticles For Performance and Functionalitymentioning
confidence: 99%
“…[ 33,34 ] PANI can improve the anti‐corrosion ability of the coating, and provide the coating with a unique scratch resistance, which can solve the problem of pitting corrosion of traditional anti‐corrosion coatings. [ 35–37 ] Our idea was to prepare tung oil‐loaded PU/PANI microcapsules. Through the synergistic action of tung oil and PANI, the polymer coating shown an excellent self‐healing and corrosion protection property to the metal.…”
Section: Introductionmentioning
confidence: 99%